Expression, purification and characterization of the recombinant ribonuclease P protein component from Bacillus subtilis. - Niranjanakumari, S (1998)
Ribonuclease P is a ribonucleoprotein complex that catalyzes the essential 5' maturation of all precursor tRNA molecules. The protein component both alters the conformation of the RNA component and enhances the substrate affinity and specificity. To facilitate biochemical and biophysical studies, the protein component of Bacillus subtilis ribonuclease P (RNase P) was overproduced in Escherichia coli using the native amino acid sequence with the initial 20 codons optimized for expression in E.coli . A simple purification procedure using consecutive cation exchange chromatography steps in the presence and absence of urea was developed to purify large quantities of P protein without contaminating nucleic acids. The identity of the recombinant protein as a cofactor of RNase P was established by its ability to stimulate the activity of the RNA component in low ionic strength buffer in a 1:1 stoichiometry. Circular dichroism studies indicate that P protein is a combination of alpha-helix and beta-sheet secondary structures and is quite stable, with a T m of 67 degrees C. The described methods facilitated the large scale purification of homogeneous, RNA-free P protein required for high resolution crystallographic analyses and may be useful for the preparation of other RNA binding proteins.